Identifikasi Senyawa Terpenoid Pada Famili Tumbuhan Euphorbiaceae Melalui Uji Kualitatif Dan Potensi Penerapan Pada Pembelajaran Biologi - Sri Handayani; Aidil Adhani; Vlorensius Vlorensius (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2022)
Indonesia is one of the countries that has a diversity of plants scattered in various tropical forests such as nursery forests and luntoh rice fields. Kroton (Codiaeum variegatum) and Patikan kebo (Euphorbia hirta L) are plant species belonging to the Euphorbiaceae family that are found in nursery forests and luntoh rice fields. The tests used in this study were histochemical tests with 5% CuSO4 reagents and glycerin, and ethanol extraction tests with concentrated HCl and concentrated H2SO4 reagents. This test is used to identify terpenoid compounds in root, stem, and leaf organs. The results of the study showed that from two plant species of the Euphorbiaceae family, there were organs containing terpenoid compounds which were scattered in various organs of roots, stems, and leaves. In the Croton plant species (Codiaeum variegatum), the organs containing terpenoid compounds are in the roots and leaves. In the Patikan kebo plant species (Euphorbia hirta L), the part of the organ containing terpenoid compounds is in the leaf. In this study, the potential for implementing learning in the form of lesson plans, practicum guides, and teaching materials.Â Keywords: Euphorbiaceae, Potential Application of Â Biology Learning, Histochemical Â Test, Ethanol Extraction Test.